Obstacles When Creating Peace in Non-western and Western Countries - Steinmetz, Carl Hermann Dino (Advances in Social Sciences Research Journal, 2025)
In an era marked by escalating geopolitical tensions, entrenched inequalities, and resurgent militarism, the pursuit of lasting peace remains an elusive yet urgent imperative. This article examines the multifaceted obstacles hindering peacebuilding efforts across Western and non-Western societies, revealing both universal and region-specific challenges. From political instability and economic disparity to ethnic divisions and external interference, systemic barriers perpetuate cycles of conflict. The analysis highlights how corruption, resource exploitation, and weak institutions undermine stability in post-colonial states, while Western nations grapple with polarization, systemic racism, and the corrosive influence of the military-industrial complex. Amid these challenges, the weaponization of misinformation and the proliferation of arms further entrench violence. Yet, the article also identifies pathways forward: inclusive governance, economic justice, and strengthened international cooperation emerge as vital mechanisms for dismantling structural inequities and fostering resilience. By addressing root causes rather than symptoms, policymakers can shift from reactive militarization to sustainable peace—a vision demanding not only institutional reform but a fundamental reimagining of global solidarity. The stakes could not be higher; in a world teetering between division and cohesion, the choice is between perpetuating cycles of violence or forging a future anchored in collective dignity and shared security.